1999
DOI: 10.1046/j.1365-2672.1999.00696.x
|View full text |Cite
|
Sign up to set email alerts
|

Resistant starch modifies gut microflora and microbial metabolism in human flora-associated rats inoculated with faeces from Italian and UK donors

Abstract: The effect of sucrose and resistant starch (‘CrystaLean’– a retrograded, amylose starch) on human gut microflora and associated parameters was studied in human flora‐associated (HFA) rats, colonized with microfloras from UK or Italian subjects, to determine whether such floras were affected differently by dietary carbohydrates. Consumption of the resistant starch diet resulted in significant changes in four of the seven main groups of bacteria enumerated. In both the UK and Italian flora‐associated rats, numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
118
1
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(124 citation statements)
references
References 39 publications
4
118
1
1
Order By: Relevance
“…RS has prebiotic properties. 36,37 Previous studies in rats have shown that as little as 10% HAS in the diet is capable of stimulating the production of desirable bacterial species like lactobacilli and bifidobacteria. 21 RS in the current study was able to induce positive changes in the luminal microenvironment such as acidification of digesta and increased faecal bulk both which may contribute to enhanced colonic health for the host.…”
Section: Discussionmentioning
confidence: 99%
“…RS has prebiotic properties. 36,37 Previous studies in rats have shown that as little as 10% HAS in the diet is capable of stimulating the production of desirable bacterial species like lactobacilli and bifidobacteria. 21 RS in the current study was able to induce positive changes in the luminal microenvironment such as acidification of digesta and increased faecal bulk both which may contribute to enhanced colonic health for the host.…”
Section: Discussionmentioning
confidence: 99%
“…In a similarly designed study, chronic ingestion of FOS did not improve GI tolerance or reduce breath hydrogen excretion in healthy subjects (Briet et al, 1995). Although adaptive metabolic changes in colonic flora have been observed in response to ingestion of different types of RS (LeBlay et al, 1999;Silvi et al, 1999), it is possible that ingestion of RRM for only 21 days was not sufficient to induce measurable adaptation effects.…”
Section: Discussionmentioning
confidence: 99%
“…Resistant starch selectively increased the levels of lactobacilli and bi dobacteria in faecal samples from rats associated with human micro ora. At the same time, it reduced caecal ammonia concentration, caecal pH and beta-glucuronidase activity (42).…”
Section: Prebioticsmentioning
confidence: 99%